Exploring the implementation and practices of the parent-coach dual role - KurtzFavero, M.; Murata, A.; Strydom, N.; Tse, T.; Costa, G. H.; Côté, J. (The Sport Psychologist, 2023)
Previous research looking into youth sport coaching indicates that a majority of coaches may also be a parent to an athlete on their team. While previous studies have also sought to understand how being a parent-coach might affect parents` relationships with their own child(ren), little work appears to explore how occupying this role might affect an individual`s ability to remain effective as a coach. As such, 14 parent-coaches were interviewed to examine how they perceived their dual role to influence their coaching effectiveness and to hear what strategies they used to remain effective. Interviews were analyzed thematically, and findings indicated that parent-coaches have few formalized resources to aid them in navigating the issues associated with their challenging dual-role position. More support would be welcomed by this population to improve their effectiveness and to ensure that all developing athletes in their care continue to have positive experiences within the youth sport environment.